Analisis Pengaruh Infrastruktur terhadap Pertumbuhan Ekonomi di Aceh - Adrisa Auldri; Rinaldi Syahputra; Yani Rizal (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of infrastructure on economic growth in Aceh. The method used in this study is quantitative, and the data will be analyzed according to the required model. Data processing is carried out using multiple linear regression, and the classical assumption tests that must be performed include the Normality Test to ensure data distribution, the Multicollinearity Test to detect correlations between independent variables, the Heteroscedasticity Test to examine residual variance, and the Autocorrelation Test to evaluate the existence of correlations between errors in the model. Eviews12 software is used, which allows for comprehensive modeling of the relationship between infrastructure variables and economic growth. The data source used is secondary data obtained from historical records found in published archives. The findings of the study reveal that road infrastructure has an insignificant negative impact on economic growth, indicating that high-quality road infrastructure improvement and maintenance are key to building an effective transportation system and supporting sustainable economic growth. Conversely, educational infrastructure has a significant positive effect on economic growth, confirming the crucial role of education in driving economic growth. On the other hand, health infrastructure has a negative but significant impact on economic growth, playing a crucial role not only from a social perspective but also in promoting economic development and community welfare. Based on regression analysis, the R2 - Squared (R2) value was recorded at 0.775876. This indicates that the independent variables can explain 77.58% of economic growth in Aceh, while the remaining 22.42% is explained by other variables not included in this study. Therefore, further research is needed to identify other variables that also contribute significantly to economic growth in Aceh.